An International Civil Law Approach to the Legal Certainty of Same-Sex Marriage with Differences in Citizenship (Case Study of Ragil Mahardika and Fred Vollert Frederik) - Nurhan, Cinta Annata; Erwanto, Nabila Mauldy; Gisna, Eva Shifdlotul; Salsabil R P, Frisca Zalfa; Sabila, Fanim Angelina (PT FORMOSA CENDEKIA GLOBAL, 2023)
The phenomenon of same-sex marriage is a phenomenon that is widely discussed in society. The marriage of Ragil Mahardika and Fred Vollert Frederik contains foreign elements when viewed from the perspective of the subjects who are citizens of different countries, Indonesia & Germany. Their marriage can be considered valid in Germany in accordance with the principle of